Correlation between Placental Thickness on Mid-trimester Ultrasound and Fetal Growth Restriction - Irum Batool Hashmi, Anila Mujadid, Shazia Aftab, Sajida Imran, Ata Ur Rehman, Ayesha Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Perinatal morbidity and mortality continue to be significant issues in all parts of the world due to fetal growth restriction. It is crucial that the risks of pregnancies should be recognized early to be followed up and taken care of in time. Thickness of the placental ultimate in regular mid-trimester ultrasound could be an indicator of placental development and placental functioning and can be used as an easy indicator to predict poor fetal growth. Objective: To evaluate the correlation between placental thickness measured on mid-trimester ultrasound and the occurrence of fetal growth restriction. Methodology: This analytical cross-sectional research was carried out in January 2022- January 2023 at Women and Children hospital MTI - DHQ Teaching Hospital, D.I. Khan. Consecutive sampling was utilised to enroll 72 singleton pregnancies with 18 to 24 weeks gestation time. The placental thickness was determined by measuring the level at which the umbilical cord would be inserted during routine scanning of anomalies. Fetal biometry was taken and estimated weight of the fetus was determined by relying on standard formula. Fetal growth restriction was considered as fetal weight that was below the 10th percentile of gestational age. Chi-square test and Pearson correlation coefficient were used as statistical methods of analysis. Results: Abnormal placental thickness was observed in 41.6% of cases. Fetal growth restriction was significantly more frequent in pregnancies with thin or thick placentas compared to those with normal placental thickness (p = 0.002). A moderate positive correlation was found between placental thickness and estimated fetal weight percentile (r = 0.41, p = 0.001). Conclusion: Placental thickness measured during mid-trimester ultrasound shows a significant association with fetal growth restriction and may serve as a useful adjunct in identifying pregnancies at risk of impaired fetal growth. Keywords: Placental thickness; Mid-trimester ultrasound; Fetal growth restriction; Estimated fetal weight; Pregnancy.